Method for preparing hyperbranched non-ionic concrete shrinkage reducing agent from modified natural biomass chitin and product and application of hyperbranched non-ionic concrete shrinkage reducing agent
By modifying natural biomass chitin polymers, hyperbranched, nonionic modified natural biomass chitin shrinkage agents are prepared by methods such as enzyme degradation, phosphorus esterification, hydroxyl ammonization and graft copolymerization, which solves the problems of poor water solubility and complex process in the preparation of traditional shrinkage agents, and achieves low-cost, high-performance and environmentally friendly concrete shrinkage agents.
Patent Information
- Application Number
- CN202411949194.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
During the preparation of traditional graft type hyperbranched shrinkage agent, there are problems such as poor water solubility, low monomer conversion, low graft rate and graft density, and complex process. In addition, the existing shrinkage agents are large in dosage, high cost, and have great impact on the early mechanical properties of concrete during use, and have environmentally friendly problems.
By modifying natural biomass chitin polymers, hyperbranched, nonionic modified natural biomass chitin reduction agents are prepared by methods such as enzyme degradation, phosphorus esterification, hydroxyl ammonization and graft copolymerization, and their water solubility, graft density and stability are improved.
It has achieved a high-performance concrete shrinking agent with low cost, low dosage, good early strength effect, strong crack resistance and environmentally friendly high performance concrete shrinking agent, which has reduced the input of production equipment and the use of organic solvents, simplified the production process, and improved the monomer conversion and yield of the shrinking agent.
Smart Images

Figure CN119684523A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass material utilization and organic water-resistant dispersant preparation, and specifically relates to a method for preparing a hyperbranched, non-ionic concrete shrinkage reducing agent by modifying natural biomass chitin, and a product and application thereof. Background Art
[0002] Compared with steel, wood, and plastic civil engineering materials, concrete has the advantages of wide material sources, low cost, strong plasticity, and simple construction. For a long time, concrete materials have remained the world's largest and most widely used civil engineering materials, and are an important material basis for the development of modern society. In the past decade, with the increasing maturity of modern civil engineering structure design theory and the increasing improvement of engineering construction technology, higher requirements have been put forward for concrete materials. The development of a high-performance concrete that is easy to pour and compact, does not segregate, can maintain the mechanical properties of concrete for a long time, and has a long service life under harsh conditions has become the main development direction of modern concrete technology. Today, high-performance concrete has been successfully used in civil engineering construction such as housing construction, highways, urban rail transit, bridge engineering, wharf engineering, airport runways, and offshore oil platforms. When preparing high-performance concrete, it is necessary to add high-efficiency water reducers to reduce the water-cement ratio of concrete and increase the fluidity of concrete, and add auxiliary cementitious materials such as fly ash, slag, and silica fume to improve the pore structure, mechanical properties, and durability of concrete. The deformation capacity of high-performance concrete is closely related to the material composition, the hydration process and hydration state of the cementitious material, and the type of hydration products. When the concrete is in a plastic state after pouring, the unhydrated cement particles and aggregates in the fresh concrete settle freely under the action of gravity, causing the solid particles to be tightly packed and the free water to move upward, resulting in the volume shrinkage of the fresh concrete in the vertical direction. When the exposed area of the fresh concrete is large, the evaporation rate of the water on the concrete surface is greater than the water seepage rate. The water in the capillaries replenishes the water consumed by evaporation, causing the liquid level in the capillary to drop, resulting in capillary negative pressure on the inner wall of the liquid. The capillary negative pressure acts as a driving force to move the water to the surface, and the surface of the fresh concrete dries rapidly and shrinks. When the cementitious material in the concrete is hydrated, the absolute volume of the hydration product is less than the sum of the absolute volumes of the cementitious material and water before hydration, causing the absolute volume of the hardened concrete material to decrease. Concrete materials are under constant temperature, constant pressure, and no external humidity exchange conditions. As the cement hydration time increases, the hydration products continue to consume capillary water. External water is not enough to compensate for the water consumption in the pores of the paste during cement hydration, resulting in a decrease in the relative humidity inside the concrete and a decrease in the liquid level of the capillary pores and gel pores, and the macroscopic volume of the hardened cement paste shrinks. High-performance concrete contains a large amount of cementitious materials. During the hydration process, a large amount of hydration heat is generated inside the concrete. The hydration heat accumulates inside the concrete, causing the temperature inside the concrete to rise. The heat diffusion causes the concrete volume to expand due to heat. As the hydration reaction gradually slows down, the temperature inside the concrete decreases, and the uneven temperature inside the concrete causes the concrete volume to shrink. After the concrete material is completely hardened, the humidity of the environment in which the concrete is located is lower than the internal humidity. The capillary water, adsorbed water, interlayer water, and chemically bound water inside the concrete evaporate to the outside, causing the radius of the meniscus of the capillary pores to decrease due to water loss. The capillary meniscus forms capillary pressure, which causes the concrete to shrink and deform during drying.High-performance concrete is also constrained by itself and adjacent components, resulting in tensile stress inside the concrete. The greater the shrinkage deformation or the stronger the constraint, the greater the tensile stress. High-performance concrete is a non-homogeneous complex multiphase composite material with lower tensile strength, flexural strength, fracture energy and greater shrinkage sensitivity than ordinary concrete. Compared with traditional concrete, the shrinkage deformation problem of high-performance concrete is more prominent. When the tensile stress inside high-performance concrete approaches or exceeds its own tensile strength, many tiny cracks and gaps will appear on the surface of the concrete. Cast-in-place concrete beams and slabs in exposed environments have cracks of varying degrees within 6-12 hours of demolding and curing. Many dam bodies and bridge decks have through cracks 2-3 days after pouring. The presence of cracks not only affects the appearance of the structure, but also has a significant adverse effect on the bearing capacity of the concrete structure. Microcracks on the concrete surface also provide channels for harmful media such as moisture, carbon dioxide, and chloride ions to invade the concrete. When the concrete structure is in a humid environment, a dry-wet alternating environment, or an area with severe acid rain or carbonation erosion, the presence of microcracks on the concrete surface significantly reduces the durability and normal use ability of the concrete and shortens the service life of the concrete structure. Under normal use conditions, the service life of high-performance concrete structures is 50-100 years. Due to the existence of cracks, many concrete structures in actual projects are destroyed after 20-30 years of use. Every year, the number of structures that are insufficiently durable and fail to meet the design requirements due to concrete cracks is huge. In the 1990s, the total value of concrete infrastructure projects in the United States reached 6 trillion US dollars. Due to the deterioration of concrete performance, the cost of reconstruction and crack repair reached 300 billion US dollars each year. Every year, there are 40,000 river dams and 800,000 small dams in the world with cracks of varying degrees. The cost of strengthening and repairing dams accounts for 10-40% of the initial investment. The durability problem of concrete structural engineering in my country is also very serious, and most buildings have a service life of less than 50 years. How to solve the cracking problem of high-performance concrete and extend the service life of structural concrete is an urgent problem to be solved in the modern concrete engineering community, which has attracted increasing attention from concrete material researchers and structural designers.
[0003] The existing measures to inhibit the shrinkage of high-performance concrete mainly include the addition of expansion agents, fibers and internal curing agents. The expansion agent method uses the expansion generated by the hydration of the expansion agent itself or the reaction with the cement hydration product to offset the shrinkage stress of concrete, thereby achieving the purpose of alleviating the shrinkage deformation of concrete. For high-performance concrete with a low water-cement ratio, the amount of mixing water in its hydration system is small, and a large amount of water has been consumed in the early cement hydration. In the later stage of cement hydration, the expansion agent cannot obtain enough water to participate in the reaction, and the expansion agent has a very limited effect on the late shrinkage compensation of high-performance concrete. In addition, this method also has the disadvantages of large expansion agent dosage (6-15% of the amount of cementitious materials) and uneconomical. The expansion agent is unstable and expands uncontrollably in a high temperature environment. When the curing temperature of a large volume of concrete mixed with the expansion agent exceeds 70°C, the high curing temperature will cause the expansion agent to decompose and the shrinkage compensation effect cannot be exerted. Adding too much expansion agent will also cause the alkali content of the concrete system to be too high, causing alkali-aggregate reaction of active aggregates in concrete. Adding fibers is another effective way to prevent concrete shrinkage cracking. Adding an appropriate amount of fiber to the concrete mixture can form a discontinuous three-dimensional mesh support system, reduce the occurrence of water seepage, prevent aggregate sinking and prevent early plastic shrinkage. The randomly distributed fibers produce a bridging effect inside the concrete. Relying on the interfacial bonding force and mechanical bite force between the fiber and the cement paste, the early elastic modulus of the concrete can be reduced, the tensile strength and toughness of the concrete can be improved, and the problems of poor early deformation resistance, large shrinkage and low tension-compression ratio of high-performance concrete can be solved within a certain range. The addition of fibers also reduces the stress gradient inside the concrete and avoids cracking caused by inconsistent shrinkage. Fibers have obvious advantages in inhibiting the plastic shrinkage and drying shrinkage of concrete. However, when adding fibers to concrete, the fiber dispersion will be poor and the working performance of the concrete will be reduced; different types of fibers have different performances. Synthetic fibers can well inhibit the plastic shrinkage of concrete, but their reinforcement effect is poor. Synthetic fibers are prone to aging and failure under the action of heat, oxygen and ultraviolet rays; non-synthetic fibers with high elastic modulus can significantly inhibit the drying shrinkage of concrete and have good reinforcement and toughening effects, but non-synthetic fiber concrete has a large relative density and is not conducive to reducing the deadweight of concrete structures. When non-synthetic fibers are used in large amounts, the fibers tend to clump and become exposed during the construction of concrete, making mixing difficult and increasing the difficulty of construction; steel fibers are easily corroded by chloride salts and rust, affecting the durability and safety of concrete; carbon fibers have high tensile strength and elastic modulus, stable chemical properties, and good adhesion to concrete, but carbon fiber concrete is prone to failure under high temperature or ultraviolet radiation and the cost of carbon fiber is high; ordinary glass fibers tend to fail in highly alkaline environments and tend to break brittlely during mixing of the mixture. These problems in the process of using fibers to improve the volume stability of concrete have restricted the promotion of fiber concrete in the field of civil engineering.Adding highly absorbent polymer internal curing agent to concrete and replenishing water from the inside of the concrete for enhanced curing is an effective method to reduce the shrinkage of concrete materials. After the internal curing agent absorbs water, it is added to the concrete to form a micro-reservoir inside the concrete. Under the action of capillary negative pressure and humidity gradient, it releases water to the cement paste to compensate for the consumed water, maintains the internal relative humidity and inhibits the shrinkage of the concrete. Highly absorbent internal curing agent has the characteristics of high water absorption, easy water loss, and effective inhibition of plastic cracking. However, high-performance concrete has fast hydration and early strength development, and its structure is relatively dense. The internal water of high-performance concrete will be quickly consumed by cement hydration, and it is easy to dry shrinkage inside. The effect of high-absorbent internal curing agent on improving the autogenous shrinkage of high-performance concrete is relatively limited. Adding excessive amounts of highly absorbent internal curing materials will also have an adverse effect on the strength of concrete. This method of inhibiting concrete shrinkage has certain limitations in its scope of use. In view of the volume stability problem of high-performance concrete materials, adding shrinkage reducers is another effective means to prevent concrete shrinkage cracking. Concrete shrinkage reducer is a water-soluble nonionic surfactant. The shrinkage reducer molecule contains polar groups and non-polar groups, and has both hydrophilic and lipophilic properties. According to the different functional groups, shrinkage reducers can be divided into monohydric alcohol (R-OH, R is alkyl), dihydric alcohol (HO-C. n H 2n -OH), polyether or polyether derivatives (R 10 OR, R is C l -C 12 Alkyl, C5-C8 cycloalkyl, phenyl), polyoxyethylene (Q[(OA) p [OR] x , R is a H group, A is a C2-C4 epoxy group, Q is a C3-C 12Aliphatic hydrocarbon functional groups, p, x are the degree of polymerization), amino alcohols and alkylamines. Polymer shrinkage reducers are composed of a variety of carbon chains, functional groups and units with different degrees of polymerization. Shrinkage reducers with different molecular structures can be designed according to the differences in performance. When the shrinkage reducer is added to the cement paste, the shrinkage reducer molecules are evenly dispersed in the water and adsorbed on the water-air interface, forming an "organic molecular film" on the surface of the cementitious material particles, which reduces the surface tension and capillary negative pressure on the water-air interface of the pore solution, and slows down the plastic shrinkage and autogenous shrinkage of the concrete. When the raw materials and mix ratio are constant, the shrinkage reducer has a better shrinkage inhibition effect on high-performance concrete with low water-cement ratio. The addition of shrinkage reducers can reduce the evaporation of water inside the concrete and keep the relative humidity inside the concrete at a higher level, which is beneficial to improve the relationship between the relative humidity and shrinkage deformation of the concrete and reduce the macroscopic shrinkage deformation of the concrete matrix. During the hydration process of concrete, the addition of shrinkage reducers reduces the concentration of alkali ions, hydroxide ions, sulfate ions and the pH value of the pore solution in the concrete system, promotes the formation of calcium hydroxide and calcium sulfonate crystals, and increases the crystallization pressure of the expansion products, causing the concrete matrix to expand, which partially offsets the deformation caused by the self-shrinkage of the concrete. Adding shrinkage reducers to inhibit concrete shrinkage overcomes the limitations of the expansion agent method and the fiber crack prevention method, provides a new way to control concrete shrinkage, and is a high-performance concrete anti-cracking technology with broad application prospects. In 1982, Japanese researchers began to develop shrinkage reducers and obtained invention patents. Subsequently, the U.S. Cement-based Materials Research Center carried out a systematic study of the functional group composition and shrinkage reduction mechanism of concrete shrinkage reducers. In 1995, the United States successfully put multi-component shrinkage reducers on the market. Such shrinkage reducers have achieved good application results in buildings, roads, bridges, tunnels, and water conservancy projects. The research work on concrete shrinkage reducers in my country started relatively late. It was not until the early 1990s that attention was paid to and research on shrinkage reducer technology. At present, scientific research institutions have developed shrinkage reducer products. The research results show that shrinkage reducers have good adaptability to cement and can play a shrinkage reduction role in different types of cement. The use of concrete shrinkage reducers is not limited by the concrete mix ratio, and can play an excellent shrinkage reduction effect under the conditions of low water-cement ratio and high cement dosage. After the shrinkage reducer is dissolved in water, the physical and chemical properties of the pore solution are changed, and the fluidity of the fresh concrete is improved. In addition to delaying the cracking time of concrete, the width of the cracks, and having a good inhibitory effect on the plastic shrinkage deformation of concrete, the addition of shrinkage reducers also significantly reduces the drying shrinkage of concrete. Adding shrinkage reducers to concrete increases the viscosity of the pore solution and reduces the porosity of concrete, improving the water absorption, chloride ion penetration resistance and freeze-thaw resistance of concrete. Considering the comprehensive performance, the shrinkage reducer method is superior to other methods of preventing concrete cracking by adding expansion agents, fibers, and internal curing agents. Therefore, expanding the scope of engineering application of shrinkage reducers is of great practical significance for improving the durability of high-performance concrete and reducing the maintenance cost of structures.
[0004] In recent years, researchers at home and abroad have carried out research on the synthesis method and application of polymer shrinkage reducers, but there are still some problems in the use of shrinkage reducers: shrinkage reducers increase the viscosity of concrete pore solution, reduce the diffusion of sulfate ions and chloride ions, the dissolution of ions in the cement hydration environment and the content of alkaline ions in the pore solution, and delay the cement hydration reaction process and slurry setting time under alkaline conditions; shrinkage reducers are not compatible with high-efficiency water reducers and expansive agents, and have a significant effect on reducing the early mechanical properties of concrete. In special cases, the early mechanical properties of concrete can be reduced by more than 15%; the amount of shrinkage reducers used in related projects in the United States is 5L / m 3 When the cost of concrete per cubic meter increases by 15.9%, the dosage of shrinkage reducer in European countries is 4kg / m 3 , the price of concrete increased by 12.20 Euros / m 3 The large dosage and high cost of shrinkage reducers are an important obstacle to the large-scale engineering application of shrinkage reducers in the concrete process; alcohol and ether shrinkage reducers have low boiling points, are volatile, flammable, and have pungent odors, and their use has negative effects on human health and the surrounding environment.
[0005] Therefore, the development of a new type of shrinkage reducer with low dosage, low cost, little effect on the early mechanical properties of concrete, good compatibility with admixtures, and environmental friendliness has become a trend and an important research direction in this field. In recent decades, researchers have tried to modify the molecules of traditional shrinkage reducers to prepare a hyperbranched polymer shrinkage reducer with a three-dimensional structure. Wen Da et al. (Synthesis and Performance Study of Hyperbranched Concrete Shrinkage Reducer, New Building Materials, 2015, 3 (18), 33-37) used shrinkage reducing groups to modify the end of hyperbranched polyamide ester containing terminal hydroxyl groups to prepare a hyperbranched concrete shrinkage reducer. Peng Lei et al. (Synthesis and Performance Study of Hyperbranched Shrinkage Reducer, New Building Materials, 2017, 9 (5), 74-78) used diethanolamine and methyl acrylate as raw materials, and synthesized a low molecular weight shrinkage reducer using succinic anhydride and polyoxyethylene alkyl ether, and synthesized a hyperbranched terminal hydroxyl polyamine-ester in one step. The end groups of the hydroxyl-terminated hyperbranched polyamine-ester are modified by using a low molecular weight shrinkage reducer, and the small molecule shrinkage reducer is grafted onto the hydroxyl-terminated hyperbranched polyamine-ester to obtain a hyperbranched polymer shrinkage reducer. Compared with traditional linear macromolecular shrinkage reducers, the three-dimensional molecular structure of the hyperbranched polymer shrinkage reducer reduces the entanglement, crystallinity, and product viscosity of the shrinkage reducer molecular chain. At high concentrations, this shrinkage reducer can still maintain a low viscosity and good solubility; with the increase of solution concentration, the surface tension of this hyperbranched shrinkage reducer solution is greatly reduced; the reduction in surface tension of the hyperbranched polymer shrinkage reducer solution of the same concentration is greater than that of the traditional shrinkage reducer solution; the three-dimensional spatial structure of the hyperbranched polymer shrinkage reducer also increases the steric hindrance of the shrinkage reducer in the concrete paste, reducing the adsorption of the shrinkage reducer molecules on the concrete cementitious material; hyperbranched, non-ionic The addition of shrinkage reducer makes the concrete pores maintain a high relative humidity and a good shrinkage reduction effect. During the exposure time of 3 and 28 days, the shrinkage value reduction rate of the hardened mortar added with 2.0% of this shrinkage reducer reaches 48.8% and 36.6%; the hyperbranched polymer shrinkage reducer has little effect on the compressive strength of cement mortar, and the long-term flexural strength of cement mortar added with this modified shrinkage reducer is also improved; the use of high molecular weight hyperbranched polymer shrinkage reducer overcomes the shortcomings of traditional low molecular weight shrinkage reducer, such as easy volatility, flammability and poor air entrainment capacity; the synthesis of this shrinkage reducer does not require separation and purification, and is suitable for large-scale industrial production. It is a new type of high-performance shrinkage reducer with broad development prospects. Although hyperbranched concrete shrinkage reducer has the above advantages, the raw materials for the preparation of hyperbranched concrete shrinkage reducer are artificial synthetic chemicals, which have limited sources and high raw material prices. The preparation of shrinkage reducing agents from etherified modified terminal hydroxyl hyperbranched polyamide esters requires the use of ethanol and isopropanol organic solvents, which have low boiling points, are volatile, flammable, and easily emit pungent odors, which have adverse effects on the surrounding environment and human health. When preparing grafted hyperbranched shrinkage reducing agents, the monomer conversion rate is low, the synthesis conditions are harsh, the synthesis conditions have a great influence on the yield, and the process is complicated.The dosage of hyperbranched shrinkage reducer is large, and the setting time of concrete containing hyperbranched shrinkage reducer is long, and the improvement effect on early mechanical properties is limited. Therefore, finding other natural biomass raw materials to prepare a natural biomass shrinkage reducer with low cost, low dosage, good early strength effect, strong crack resistance and environmental friendliness has become a hot topic in this research field.
[0006] Chitin is a natural high molecular polymer formed by N-acetyl-2-amino-2-deoxy-D-glucose connected by β-(l,4) glycosidic bonds. It belongs to amino polysaccharides and is the second largest natural high molecular compound in nature after cellulose. It is widely found in the shells of arthropods (lobsters, crabs, locusts, butterflies, centipedes, cockroaches), plant (yeast, mold, mushroom) cell walls, mollusks (earthworms, snails, horned shells, squids), protozoa (amoeba, paramecium) and coelenterates (tube hydra, moon jellyfish, nematodes) epidermis and bones. The annual global production of natural chitin is as high as 100 billion tons, and marine organisms synthesize chitin to more than 9 billion tons. Natural chitin polymers have good biocompatibility, biodegradability, abundant sources and low raw material costs. It is an inexhaustible natural resource. The chitin molecule is composed of four elements: C, H, O, and N, and the chemical formula is (C8H 13 NO5) n , its relative molecular mass is 3×10 5 -7×10 5. The 2-carbon of the chitin polymer molecule is connected to an acetylamino group (-NHCOCH3), and the 3-carbon and 5-carbon are connected to a hydroxyl group (-OH) and a hydroxymethyl group (-CH2OH). The presence of the acetylamino, hydroxyl and hydroxymethyl groups makes it easy for chitin molecules to form strong polar hydrogen bonds within and between molecules, making the crystal structure of chitin very regular. The steric hindrance effect between adjacent glucose residue bonds in the chitin molecule reduces the rotational freedom of the glucose residue bonds, and the chitin molecule presents a compact microfiber network structure. Chitin polymers are insoluble in water, dilute acids, alkalis, ethanol and most organic solvents, and are only soluble in concentrated hydrochloric acid, concentrated sulfuric acid, 75-78% phosphoric acid and anhydrous formic acid. Direct use of chitin polymer as a reaction monomer has poor water solubility, large relative molecular weight, and poor bridging ability, which affects the performance and effect of chitin polymer materials. It is necessary to degrade, oxidize, etherify, esterify, crosslink, and graft to modify the natural chitin molecules to introduce active substituents, change the chitin molecular structure, give natural biomass chitin materials better performance, and expand the application field of chitin materials. Under the action of enzyme mediators, the β-(l,4) glycosidic bonds on the main chain skeleton of the linear chitin polymer break and degrade, resulting in a decrease in the molecular weight of the chitin polymer and a change in the crystalline structure, which improves the solubility, moisture retention and film-forming properties of the chitin molecules in water. The activity of the hydroxymethyl on the C5 carbon of the D-glucose residue of the chitin molecule is greater than that of the C3 hydroxyl group. Under the action of oxidants, the C5 hydroxymethyl of chitin can be oxidized to aldehyde and carboxyl groups, and the C3 hydroxyl group can be oxidized and degraded to low molecular weight oxidized chitin. Oxidized chitosan products have the advantages of good solubility, strong temperature resistance, salt resistance, shear degradation resistance, good storage capacity, and strong moisture absorption capacity. Acylation modification of chitosan polymers is a common chemical modification method. Chitosan polymers are acylated with acyl chlorides or anhydrides to introduce aliphatic or aromatic acyl groups into the chitosan macromolecular chain, which destroys the hydrogen bonds between chitosan macromolecules, improves the crystalline structure of chitosan polymers and the solubility of chitosan materials in organic solvents, and improves the molding and processing properties of acylated chitosan derivatives. The active hydroxymethyl and hydroxyl groups in chitosan polymer molecules react with etherification agents to generate methyl ether, ethyl ether, benzyl ether, hydroxyethyl ether, and hydroxymethyl ether. Etherification treatment of chitosan polymers reduces the number of hydrogen bonds in chitosan molecules, increases the solubility of chitosan in water and organic solvents, increases the charge density of cationic electrolytes, and gives chitosan polymers better compatibility, biodegradability, high pressure resistance, and high temperature resistance. The active hydroxyl group at position C3 on the D-glucose residue in the chitin molecule can react with organic or inorganic acids to undergo sulfation and phosphate reactions. Chitin derivatives modified by chlorosulfonic acid, concentrated sulfuric acid, perchloric acid, acetic acid, organic acid and phosphate have the characteristics of good heat resistance, heavy metal ion adsorption, complexation or ion exchange ability. The alcoholic hydroxyl group in the chitin molecule is also easy to chemically cross-link with binary or polyfunctional groups to prepare high molecular polymer gels and films with a network structure.Chemical cross-linking reactions improve chitin's biodegradability, water solubility, film-forming strength, shear resistance, viscosity resistance, heat resistance, and swelling resistance, making the modified chitin have excellent heavy metal adsorption capacity. By grafting vinyl monomers and other double-bond monomers onto the D-glucose main chain unit of the chitin molecule through an initiator, the molecular weight of the product and the amount of cationic charge on the molecule can be increased, the molecular structure properties of chitin can be changed, and chitin can be given more and better functions. Chitin graft copolymers show excellent water solubility, complexing properties, flocculation properties, physical brittleness, and heat sensitivity, which expands the scope of use of natural chitin polymer materials. Chemical modification of natural chitin polymers is the most active direction in the field of natural chitin material research. Summary of the invention
[0007] Purpose of the invention: The technical problem to be solved by the present invention is the poor water solubility of the product, low monomer conversion rate, low grafting rate and grafting density, and complex process in the preparation process of traditional grafted hyperbranched shrinkage reducing agents.
[0008] The present invention also aims to solve the technical problem of providing a method for preparing a low-cost, biodegradable, green and environmentally friendly, simple process and high-performance hyperbranched, non-ionic modified natural biomass chitosan concrete shrinkage reducing agent.
[0009] The final technical problem to be solved by the present invention is to provide the application of hyperbranched, non-ionic modified natural biomass chitosan shrinkage reducing agent in concrete.
[0010] Technical solution: In order to solve the above technical problems, the present invention provides a method for preparing a hyperbranched, non-ionic concrete shrinkage reducing agent by modifying natural biomass chitosan, comprising the following steps:
[0011] (1) heating and stirring a chitosan polymer and water to obtain a suspension, acidifying the suspension and then treating it with chitinase to obtain a chitosan oligomer solution, wherein the weight average molecular weight of the chitosan oligomer is controlled to be between 8435 and 8678;
[0012] (2) adding sodium dihydrogen phosphate to the chitosan oligomer solution and adjusting the pH value to 2-3, causing a phosphating reaction in a microwave reactor to obtain chitosan phosphate derivative oligomers, taking out the chitosan phosphate oligomer solution from the microwave reactor after the reaction, heating it to 65-70° C., adding sodium hydroxide solution to adjust the pH value of the system to 12-13, rapidly stirring at 65-70° C. for 8-10 hours, removing the acetyl group in the chitosan phosphate oligomer, and obtaining a chitosan oligomer solution containing amino groups and phosphate ester groups, and controlling the deacylation degree of the chitosan phosphate oligomer molecules to be 88-92%;
[0013] (3) slowly adding the chitosan oligomer solution containing amino groups and phosphate groups prepared in step (2) to the methyl allyl alcohol polyoxyethylene ether solution, and completing the addition over 30-40 minutes, slowly adding the catalyst p-toluenesulfonic acid, and raising the temperature to 120-130° C. At this temperature, the hydroxyl groups on the methyl allyl alcohol polyoxyethylene ether and the amino groups on the phosphate chitosan oligomer undergo hydroxylation reaction for 6-8 hours to obtain a light yellow oily chitosan oligomer solution containing double bonds, phosphate groups, and ether groups;
[0014] (4) adding the chitosan oligomer solution containing double bonds, phosphate groups and ether groups prepared in step (3) to the 1,2-epoxy-4-vinylcyclohexane aqueous solution at a temperature of 40-45° C., stirring continuously, adjusting the pH value of the system to 10-11, maintaining the solution temperature at 65-70° C., slowly adding ammonium persulfate and manganese pyrophosphate composite initiator dropwise over 20-30 minutes, raising the system temperature to 90-95° C., and graft copolymerizing at 90-95° C. for 3-4 hours;
[0015] (5) After the reaction is completed, the reactant solution is naturally cooled to ambient temperature, and then matured in a reaction vessel for 2-3 hours, and the pH value is adjusted to 10-11 to prepare a light yellow hyperbranched, non-ionic modified natural biomass chitosan shrinkage reducing agent with a solid content of 15-18% and containing -OH, -NH2, -OPO3Na, -R1OR2, and -CH2(O)CH2 groups.
[0016] Wherein, the weight ratio of chitosan polymer to water in step (1) is 1:1.6; the acidification reaction temperature is 25-30°C, the pH is 4-5, and the acidification treatment takes 20-30 minutes.
[0017] Wherein, the amount of chitinase in step (1) is 2.45-2.50wt% (weight percentage) of the amount of chitin polymer, the chitinase treatment temperature is -5-0°C, and stirring is continued for 8-10 hours.
[0018] Wherein, in step (2), the weight ratio of the chitosan oligomer solution to sodium dihydrogen phosphate is 39.5:1-40.0:1, the radiation reaction power of the microwave reactor is 150W, the maximum radiation reaction temperature is 95°C, and the radiation reaction time is 20 minutes.
[0019] Wherein, in step (3), the weight ratio of methyl allyl alcohol polyoxyethylene ether to the chitosan oligomer solution containing amino and phosphate groups is 1:2.75-2.80, and the amount of p-toluenesulfonic acid used is 2.23-2.24wt% (weight percentage) of the amount of methyl allyl alcohol polyoxyethylene ether used.
[0020] Wherein, in step (4), the weight ratio of 1,2-epoxy-4-vinylcyclohexane to the chitosan oligomer solution containing double bonds, phosphate groups, and ether groups is 1:60.1-60.2, the amount of ammonium persulfate and manganese pyrophosphate composite initiator is 1.50-1.51wt% of the amount of the chitosan oligomer solution containing double bonds, phosphate groups, and ether groups, and the ratio of ammonium persulfate to manganese pyrophosphate is 1:1 (weight ratio).
[0021] Wherein, step (5) also includes placing the modified natural biomass chitosan shrinkage reducing agent solution in an oven, drying it at a temperature of 90-95° C. for 16-24 hours to obtain a solid shrinkage reducing agent, crushing and ball-milling the solid shrinkage reducing agent, and passing it through a 0.40 mm round hole sieve to obtain a modified natural biomass chitosan shrinkage reducing agent powder with a particle size of less than 0.40 mm.
[0022] The present invention also includes the use of the modified natural biomass chitosan shrinkage reducing agent in the preparation of concrete.
[0023] Wherein, the modified natural biomass chitosan shrinkage reducing agent is added in an amount of 0.5-2.0wt%.
[0024] The mechanism of the present invention includes: the present invention starts with the molecular structure of chitin polymer and the molecular design of shrinkage reducing agent, with the purpose of improving the water solubility, the number of ether groups and epoxy groups, the grafting rate and the grafting density, and the charge amount of the modified natural chitin product. The shrinkage reducing agent is prepared using natural chitin polymer, biological enzyme, phosphate, monomethyl ether containing double bonds, and epoxyalkane containing double bonds as raw materials. Under the action of chitinase, the molecular chain of the natural chitin polymer is broken and the degree of polymerization is reduced to obtain chitin oligomers. The hydroxyl groups on the C3 and C5 carbons on the chitin oligomer molecules react with the phosphide to obtain phosphate chitin oligomers. Under the action of strong alkali, the acetylamino groups on the phosphate chitin oligomer derivatives react to deacylate, so as to obtain chitosan oligomers containing amino groups and phosphate groups. The amino groups on the chitosan oligomer containing phosphate groups and the hydroxyl groups on methyl allyl alcohol polyoxyethylene ether reacted with alcohol amination to introduce double bonds into the phosphate chitosan oligomer molecules. Under the action of a composite chain initiator, the chitosan oligomer methyl ether containing double bonds phosphate groups and 1,2-epoxy-4-vinylcyclohexane monomers underwent graft copolymerization to prepare a hyperbranched, non-ionic concrete shrinkage reducer containing hydroxyl groups (-OH), amino groups (-NH2), phosphate groups (-OPO3Na), epoxy groups (-CH2(O)CH2), and ether groups (-R1OR2). The natural chitin polymer was enzymatically degraded to improve the water solubility and hydroxyl reactivity of the chitin polymer. The introduction of phosphate groups into the side chains of the modified chitin oligomer molecules through phosphoesterification reaction can improve the water solubility of the product and adjust the hydrophilic-lipophilic balance value of the shrinkage reducer, thereby improving the stability and wetting effect of the shrinkage reducer in the concrete pore fluid. The graft copolymerization of phosphate chitosan oligomer methyl ether containing double bonds and 1,2-epoxy-4-vinylcyclohexane monomer effectively increases the graft density, charge and product molecular weight of the shrinkage reducer molecule. The introduction of oxyethylene groups with large steric hindrance in the side chain of the shrinkage reducer molecule also reduces the adsorption of mud particles. The ether bonds on the oxyethylene groups form hydrogen bonds with water molecules and adsorb on the shrinkage reducer molecules, preventing the volatilization of water and reducing the shrinkage of concrete. The use of natural chitin polymers to prepare shrinkage reducers has broadened the application field of natural chitin polymers and reduced the use of fine chemicals and raw material costs in the preparation of shrinkage reducers. The use of hyperbranched graft copolymerization to prepare shrinkage reducers also reduces the amount of organic solvents used in the preparation process, simplifies the production process and production technology, avoids the negative impact of organic solvents and hazardous chemicals on the surrounding environment and human health, and improves the conversion rate and yield of shrinkage reducer monomers. The prepared modified natural biomass chitin hyperbranched, non-ionic shrinkage reducer has high water stability, is not easily affected by strong electrolytes and acids and alkalis, and does not strongly adsorb on the surface of cementitious materials. Concrete added with this shrinkage reducer has the characteristics of low dosage, short setting time, small loss of early mechanical properties and good deformation resistance. It meets the requirements of low cost, biodegradability and green environmental protection of modern high-performance shrinkage reducers, has good economic, social and environmental value, and has broad application prospects.
[0025] Beneficial effects: Compared with the prior art, the hyperbranched, nonionic modified natural biomass chitosan shrinkage reducing agent prepared by the present invention has the following advantages:
[0026] (1) Compared with traditional shrinkage reducers, the use of natural chitin polymers to prepare shrinkage reducers consumes a large amount of natural biomass chitin materials and broadens the application field of natural chitin polymer materials. This preparation method reduces the amount of acrylic acid, methyl acrylate, and succinic anhydride monomers used in the shrinkage reducer production process. According to Example 1 of the present invention, the production of one ton of this modified natural biomass chitin shrinkage reducer can save 95.6 yuan in shrinkage reducer raw material costs and transportation costs. This preparation method also reduces the use of organic solvents such as ethanol and isopropanol in production. The production of one ton of this modified natural biomass chitin shrinkage reducer can save 4.67 yuan in organic solvent usage fees.
[0027] (2) The aqueous phase homogeneous method is used to prepare the modified natural biomass chitosan shrinkage reducing agent, which simplifies the preparation steps of the traditional shrinkage reducing agent and overcomes the problems of harsh synthesis conditions, low yield and complex process of the traditional shrinkage reducing agent. This modified natural chitosan shrinkage reducing agent preparation method can reduce the investment in production equipment and equipment usage fees by 74,900 yuan. Due to the simplified production process and production process, the production time can be shortened by 2-3 hours. According to Example 1 of the present invention, one ton of this modified natural biomass chitosan shrinkage reducing agent can save 8.33 yuan in labor costs and time costs.
[0028] (3) This shrinkage reducing agent preparation method reduces the use of artificial chemicals such as acrylic acid, methyl acrylate, and succinic anhydride and organic solvents such as ethanol and isopropanol, and reduces the adverse effects of the volatility and irritating odor emissions of artificial chemicals during the shrinkage reducing agent production process on the surrounding environment and human health, thereby achieving green production of shrinkage reducing agents.
[0029] (4) The natural chitin polymer molecules are modified by introducing hydroxyl, amino, phosphate, ether and epoxy groups into the chitin molecular chain, thereby improving the water solubility, the number of ether and epoxy groups, the grafting rate, the charge, the hydrophilic-lipophilic balance, the stability and the wetting effect of the modified natural biomass chitin shrinkage reducer product, reducing the adsorption of the shrinkage reducer on cement particles and preventing the volatilization of water in the concrete pores.
[0030] (5) Under the same crack-resistance effect, the modified natural biomass chitosan shrinkage reducer has a lower dosage than the traditional shrinkage reducer. According to Example 1 of the present invention, the shrinkage reducer usage fee of 2.56 yuan can be saved per cubic meter of concrete.
[0031] (6) Adding the modified natural biomass chitosan shrinkage reducer to the concrete material can reduce the negative impact of the shrinkage reducer on the hydration of the cementitious material in the concrete material, the setting time of the cement paste, and the early mechanical strength of the concrete, improve the volume stability and durability of the concrete, and extend the service life of the concrete structure. According to Example 1 of the present invention, the construction and maintenance costs of each cubic meter of the concrete structure can be saved by 2.01 yuan.
[0032] In summary, according to the method of Example 1 of the present invention, if 8,000 tons of such modified natural biomass chitosan shrinkage reducing agent are produced annually, the raw material and organic solvent usage fees can be saved by 802,200 yuan. The economic benefits of 141,500 yuan can be generated by reducing the investment in production equipment, equipment usage fees, simplifying the process, reducing production time and labor costs. 8,000 tons of such shrinkage reducing agent can be used to prepare 4.05×10 5 The reduction agent usage fee can be saved by RMB 1,036,800, and the cost of concrete structure construction and maintenance can be saved by RMB 814,100. If 8,000 tons of modified natural biomass chitosan reduction agent is produced annually, a total economic benefit of RMB 2,794,600 can be generated. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A flow chart for preparing a hyperbranched, nonionic modified natural chitin shrinkage reducing agent;
[0034] Figure 2 It is a diagram of the foaming performance of the solution mixed with modified natural chitosan biomass shrinkage reducing agent and the solution mixed with commercial shrinkage reducing agent;
[0035] Figure 3 The surface tension diagram of the solution of modified natural chitosan biomass shrinkage reducing agent with different concentrations and the solution of commercial shrinkage reducing agent;
[0036] Figure 4 The figure is a comparison of the initial slump expansion and slump expansion retention of concrete mixed with modified natural chitosan biomass shrinkage reducing agent and concrete mixed with commercial shrinkage reducing agent;
[0037] Figure 5 It is a comparison chart of the setting time of concrete mixed with modified natural chitosan biomass shrinkage reducing agent and concrete mixed with commercial shrinkage reducing agent;
[0038] Figure 6 It is a comparison chart of the compressive strength of concrete mixed with modified natural chitosan biomass shrinkage reducing agent and concrete mixed with commercial shrinkage reducing agent;
[0039] Figure 7 It is a comparison chart of the flexural strength of concrete mixed with modified natural chitosan biomass shrinkage reducing agent and concrete mixed with commercial shrinkage reducing agent;
[0040] Figure 8This is a comparison chart of the crack resistance of concrete mixed with modified natural chitosan biomass shrinkage reducing agent and concrete mixed with commercial shrinkage reducing agent;
[0041] Fig. 9 Comparison of the autogenous shrinkage values of concrete mixed with modified natural chitosan biomass shrinkage reducer and concrete mixed with commercial shrinkage reducer;
[0042] Fig.10 Comparison of drying shrinkage values of concrete mixed with modified natural chitosan biomass shrinkage reducer and concrete mixed with commercial shrinkage reducer;
[0043] Fig.11 Comparison of water absorption of hardened concrete mixed with modified natural chitosan biomass shrinkage reducer and hardened concrete mixed with commercial shrinkage reducer;
[0044] Fig.12 Comparison of the resistance to chloride ion penetration of hardened concrete mixed with modified natural chitosan biomass shrinkage reducer and hardened concrete mixed with commercially available shrinkage reducer. DETAILED DESCRIPTION
[0045] One ton of hyperbranched, nonionic modified natural chitin biomass shrinkage reducer (M-Chitin-SRA) was produced according to the preparation method described in the embodiment of the present invention, and the application research of fresh mix performance, mechanical properties, crack resistance, shrinkage performance and durability of concrete added with this shrinkage reducer was carried out, and the performance of concrete added with a commercially available shrinkage reducer (SITREN-SRA, industrial grade, Shanghai Evonik Specialty Chemical Co., Ltd.) was compared.
[0046] The sources of raw materials and reagents used in the examples of the present invention are as follows:
[0047] Natural chitosan polymer (weight-average molecular weight 335,400) was produced by Nantong Langshan Xingcheng Biochemical Products Factory; dilute hydrochloric acid (industrial grade, 37% concentration) was produced by Yangzhou Huafu Chemical Co., Ltd.; chitinase powder (industrial grade, purity 99%) was produced by Shandong Fuwangjia Biotechnology Co., Ltd.; sodium dihydrogen phosphate (industrial grade, purity above 98%) was produced by Jiangsu Kelunduo Food Ingredients Co., Ltd.; glacial acetic acid (industrial grade, purity 97%) was produced by Shandong Lanxing New Materials Co., Ltd.; sodium hydroxide (industrial grade, concentration 20%) was produced by Hebei Cangzhou Xincheng Chemical Products Co., Ltd. Produced by; methyl allyl alcohol polyoxyethylene ether (TPEG-2400, industrial grade, purity 99%) was produced by Zhejiang Royal Madrid Technology Co., Ltd.; p-toluenesulfonic acid (industrial grade, purity 95%) was provided by Shanghai Feige Co., Ltd.; 1,2-epoxy-4-vinylcyclohexane (analytical grade, purity ≥99%) was produced by Shanghai Sigma-Aldrich Chemical Co., Ltd.; ammonium persulfate (industrial grade, purity 90.0-91.0%) was produced by Fujian Zhanhua Chemical Co., Ltd.; manganese pyrophosphate (industrial grade, purity ≥92.5%) was produced by Fujian Zhanhua Chemical Co., Ltd.
[0048] Example 1 Preparation of hyperbranched, nonionic modified natural chitosan biomass shrinkage reducing agent
[0049] 1. Degradation of chitin polymer
[0050] Weigh 175kg of natural chitin polymer and 280kg of water into a reactor equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, and accelerate the stirring for 120 minutes to evenly disperse the chitin polymer in the water to form a uniform suspension solution. At 30°C, dilute hydrochloric acid was used to adjust the pH value of the suspension to 4.76, and the acidification was carried out for 30 minutes. 4.35kg of light yellow chitinase powder and 45kg of water were mixed and shaken for 8 minutes to form a uniform chitinase solution. Chitinase solution was added to the chitin suspension solution, placed in a refrigerator at a temperature of -5-0°C and stirred continuously for 10 hours. Under the action of chitinase, the chitin polymer was degraded to obtain 492.54kg of milky white chitin oligomer solution. The molecular weight of chitin oligomer was determined by gel permeation chromatography, and the weight average molecular weight of chitin oligomer was measured to be 8516.
[0051] 2. Preparation of chitosan oligomers containing amino and phosphate groups
[0052] Weigh 487.5kg chitosan oligomer solution and 12.25kg sodium dihydrogen phosphate into a reactor equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, mix and stir to form a uniform solution, and add glacial acetic acid to adjust the pH value of the system to 2.58. The mixed solution is placed in a microwave radiation organic synthesis reactor, and the system control software is set to set the microwave radiation power to 150W, the maximum radiation reaction temperature to 95°C, and the radiation reaction time to 20 minutes. After the microwave reaction is completed, the chitosan phosphate oligomer solution is taken out from the microwave reactor, cooled to 70°C, and 20% sodium hydroxide solution is added to adjust the pH value of the system to 12.52. Stir at 70°C for 8 hours to remove the acetyl group in the chitosan phosphate oligomer to obtain 475.76kg chitosan oligomer solution containing amino and phosphate groups. The deacylation degree of the chitosan phosphate oligomer molecule is 89.74%.
[0053] 3. Etherification reaction of chitosan oligomers containing amino and phosphate groups
[0054] Put 162.5kg of methyl allyl alcohol polyoxyethylene ether and 382.5kg of water into a reactor equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, mix thoroughly and continue stirring for 30 minutes to form a uniform solution. Maintaining the temperature at 45°C, slowly drop 452.5kg of chitosan oligomer solution containing amino and phosphate groups into the methyl allyl alcohol polyoxyethylene ether solution, and add it in 40 minutes. Slowly add 3.625kg of p-toluenesulfonic acid, and raise the system temperature to 130°C. At this temperature, the hydroxyl groups on the methyl allyl alcohol polyoxyethylene ether and the amino groups on the phosphate chitosan oligomer undergo hydroxyamination reaction for 8 hours to obtain 984.2kg of light yellow oily chitosan oligomer solution containing double bonds, phosphate groups, and ether groups.
[0055] 4. Preparation of hyperbranched, nonionic modified natural chitosan bio-based shrinkage reducing agent
[0056] 15.75kg 1,2-epoxy-4-vinylcyclohexane and 36.25kg water were placed in a reactor equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, and stirred continuously to form an aqueous solution. At 45°C, 947.5kg chitosan oligomer solution containing double bonds, phosphate groups, and ether groups was added to the 1,2-epoxy-4-vinylcyclohexane aqueous solution and stirred continuously for 20 minutes. 1,2-epoxy-4-vinylcyclohexane and chitosan oligomer solution containing double bonds, phosphate groups, and ether groups were mixed into a uniform solution, and the pH value of the system was adjusted to 10.56 with 20% sodium hydroxide. Keeping the solution temperature at 70°C, 14.225kg ammonium persulfate and manganese pyrophosphate composite initiator (ammonium persulfate: manganese pyrophosphate = 1:1, weight ratio) was slowly added dropwise, and the addition was completed within 25 minutes. The temperature was raised to 95°C, and graft copolymerization was carried out at 95°C for 4 hours. After the reaction is completed, the product solution is naturally cooled to ambient temperature and matured in the reactor for 3 hours. 20% sodium hydroxide is added to adjust the pH value to 10.21, and 999.23 kg of light yellow hyperbranched, non-ionic modified natural biomass chitin shrinkage reducer containing -OH, -NH2, -OPO3Na, -R1 OR2, -CH2(O)CH2 groups with a solid content of 17.14% is prepared. The modified natural biomass chitin shrinkage reducer solution is placed in an oven and dried at 95°C for 18 hours to obtain a solid modified natural biomass chitin shrinkage reducer. Crushed, ball milled, and passed through a 0.40mm round hole sieve to obtain a modified natural biomass chitin shrinkage reducer powder (M-Chitin-SRA) with a particle size less than 0.40mm.
[0057] Example 2 Physical and Chemical Properties of Hyperbranched, Non-ionic Modified Natural Chitosan Bio-based Shrinkage Reducing Agent Solution 1. Foaming Properties
[0058] The foaming ability and foaming stability of the shrinkage reducer solution were determined using a Roche foam instrument. 1.0 g of hyperbranched, non-ionic modified natural chitin bio-based shrinkage reducer powder (M-Chitin-SRA) and SITREN-SRA shrinkage reducer were placed in a volumetric flask, and water was added to 1000 mL scale and shaken. The shrinkage reducer sample solution was used to rinse the wall of the Roche foam instrument dropper tube. The Roche foam instrument containing the shrinkage reducer solution was placed on a tube rack, perpendicular to the scale section to ensure that the solution flowed to the center of the graduated cylinder. The piston switch on the Roche foam instrument dropper was turned on, so that the shrinkage reducer solution dripped into a 500 mL graduated cylinder (the measuring cylinder contained 50 mL of shrinkage reducer solution of the same concentration) through a piston tube with an inner diameter of 2.9 mm. After the shrinkage reducer solution was added, the initial foaming height of the solution and the foaming height after standing for 5 minutes were measured.
[0059] Figure 2 Shown is the foaming performance of a solution mixed with a modified natural chitosan biomass shrinkage reducing agent and a solution mixed with a commercial shrinkage reducing agent. Figure 2It can be seen that with the increase of foaming time, the foam height of both shrinkage reducer solutions decreases. At the same shrinkage reducer dosage and foaming time, the solution with modified natural chitosan biomass shrinkage reducer has a larger foam height and better foaming stability than the solution with commercial shrinkage reducer.
[0060] 2. Surface tension
[0061] Surface tension is an important aspect of characterizing the physical and chemical properties of shrinkage reducer solutions. Referring to the Test Method for Homogeneity of Concrete Admixtures (GB / T 8077-2000), the surface tension of the shrinkage reducer solution was measured using a DCAT11 surface tension meter (produced by Dataphysics Instrument Co., Ltd., Germany, with a measurement range of 1-1000mN / m and an accuracy of ±0.001mN / m). First, (M-Chitin-SRA) and SITREN-SRA shrinkage reducer solutions with concentrations of 0%, 0.5%, 1.0%, 1.5%, and 2.0% were prepared respectively. Then, the prepared shrinkage reducer solution was placed in a test container, and the platinum-iridium ring on the surface tension analyzer was in contact with the prepared shrinkage reducer solution, forming a liquid film inside the platinum-iridium ring. Finally, the platinum-iridium ring was slowly lifted from the shrinkage reducer solution until the platinum-iridium ring was pulled off the surface of the shrinkage reducer solution. At this time, the reading on the dial of the surface tension meter is the surface tension value of the shrinkage reducer solution.
[0062] Figure 3 The surface tension of the solution containing modified natural chitosan biomass shrinkage reducer and the solution containing commercial shrinkage reducer at different concentrations is shown. Figure 3 As can be seen in the figure, as the concentration of the two shrinkage reducing agent solutions increases, the surface tension continues to decrease. At the same shrinkage reducing agent concentration, the solution mixed with the modified natural chitosan biomass shrinkage reducing agent has a lower surface tension than the solution mixed with the commercial shrinkage reducing agent.
[0063] Example 3 Preparation and performance test of concrete with hyperbranched, non-ionic modified natural chitosan bio-based shrinkage reducing agent 1. Mix ratio of concrete
[0064] The cement used in this experiment is P.O42.5 ordinary Portland cement (OPC) produced by Huaxin Cement Co., Ltd., with a specific surface area of 3518 cm 2 / g, density is 3.07g / cm 3 Its performance meets the requirements of General Portland Cement (GB 175-2007). Fly ash (FA) is Class I fly ash produced by Nanjing Thermal Power Plant, with an apparent density of 2234kg / m 3 The water requirement ratio is 93.9%. The coarse aggregate is 5-25mm continuously graded basalt crushed stone from Jurong, Jiangsu, with a mud content of 0.29%, a water content of 0.76%, and an apparent density of 2620kg / m 3, the bulk density is 1954kg / m 3 The crushing value is 18.97%. The fine aggregate is river sand from Jiangxi Ganjiang II District, with a fineness modulus of 2.18, a mud content of 1.5%, a water content of 0.61%, and an apparent density of 2642kg / m 3 , bulk density is 1523kg / m 3 . Mixing water is tap water. The concrete design strength grade is C50, cementitious materials (cement + fly ash): coarse aggregate: fine aggregate: water = 1:2.37:1.25:0.36 (weight percentage). The total amount of cementitious materials in one cubic meter of concrete is 485kg, the proportion of fly ash replacing cement is 20%, the sand ratio is 34.5%, and the amount of shrinkage reducer is the weight percentage of the total cementitious materials. The mix ratio of C50 concrete used in the test is shown in Table 1. The properties of blank concrete, concrete with 0.5% (0.5%-M-Chitin-SRA), 1.0% (1.0% M-Chitin-SRA), 1.5% (1.5% M-Chitin-SRA), 2.0% (2.0% M-Chitin-SRA) modified natural chitin biomass shrinkage reducer, and concrete with 0.5% (0.5%-SITREN-SRA), 1.0% (1.0%-SITREN-SRA), 1.5% (1.5%-SITREN-SRA), 2.0% (2.0%-SITREN-SRA) commercially available shrinkage reducer were measured.
[0065] Table 1 Concrete experimental mix ratio
[0066]
[0067] 2. Preparation and maintenance of concrete
[0068] 388kg cement and 97kg fly ash were put into a mixer and mixed at a stirring speed of 40 rpm for 3 minutes. 605kg river sand fine aggregate and 1150kg crushed stone coarse aggregate were added, and stirring was continued for 1 minute at a speed of 30 rpm. 0-9.70kg modified natural chitin biomass shrinkage reducer powder (M-Chitin-SRA) (0kg, 2.425kg, 4.85kg, 7.275kg, 9.70kg) was dissolved in 174.6kg mixing water and added to the mixer, and stirred at a speed of 60 rpm for 2 minutes. To avoid the mixture from stratifying at the bottom of the container, the slurry was manually stirred twice with a shovel, and continued to mix at a speed of 60 rpm for 2 minutes. After measuring the initial slump flowability, slump flow retention and setting time of the fresh concrete mixed with the modified natural chitin biomass shrinkage reducer, the fresh concrete mixed with the M-Chitin-SRA shrinkage reducer was vibrated and compacted for 30 seconds. The vibrated and compacted fresh concrete was poured into 100mm×100mm×100mm and 150mm×150mm×550mm molds to prepare 24 specimens, and the compressive strength and flexural strength of the concrete were tested at 3, 7, 28, and 90 days. Other M-Chitin-SRA fresh concrete was poured into three 600mm×600mm×63mm thin plate molds. A polytetrafluoroethylene sheet isolation layer was laid on the bottom plate, and restraining steel bars were embedded around the mold. The concrete specimens were immediately covered with plastic film after pouring and placed in an environment with a temperature of 20±2℃ and a humidity of 60±5% for 2 hours. The plastic film was removed and the concrete surface was dried with an electric fan. The wind direction was 100mm above the center of the specimen surface, and the fan speed was 5±0.5m / s. The cracking of the concrete specimens was observed for 24 hours. Pour the rest of the freshly mixed M-Chitin-SRA concrete paste into three 100mm×100mm×515mm test molds, seal them with plastic wrap, and place them at 20±2℃ to measure the concrete shrinkage value. Pour the rest of the freshly mixed M-Chitin-SRA concrete paste into three 75mm×75mm×285mm test molds to test the concrete drying shrinkage. Pour the remaining freshly mixed concrete paste into 12 specimens were prepared in the mold, and the water absorption rate and electrical flux of hardened concrete were tested for 28 and 90 days. All concrete test molds filled with M-Chitin-SRA shrinkage reducer were covered with wet sacks and placed in an indoor environment at a temperature of 18-22°C for 24 hours. The specimens were removed from the test molds and placed in a standard curing room (temperature of 25°C, humidity of 90±5%) for curing to the specified age. Under the same conditions, the same number of concrete specimens with commercial shrinkage reducer (SITREN-SRA) were prepared for comparative experiments.
[0069] 3. Concrete performance test method
[0070] 3.1. Fresh concrete performance test
[0071] 3.1.1. Initial slump flow and slump flow retention of fresh concrete
[0072] Wipe the conical slump test cylinder with a damp cloth and place it on a horizontal steel plate. The concrete with M-Chitin-SRA shrinkage reducer and the concrete with commercial shrinkage reducer (SITREN-SRA) were respectively loaded into the slump test cylinder in three layers. After each layer of sample was loaded, the concrete was evenly rammed from the edge to the center 25 times using a vibrator. After the concrete was filled and tamped, the concrete surface was smoothed, the slump cylinder was gently lifted vertically, and the fresh concrete flowed freely on the steel plate. After the fresh concrete stopped flowing, the slump flow expansion values of the fresh concrete mixture in two mutually perpendicular directions were measured, and the average value was taken as the initial slump flow of the fresh concrete. In order to determine the slump flow retention of the fresh concrete, after the initial slump flow test of the concrete was completed, the concrete sample was placed in an iron bucket and sealed and left to stand for 30, 60, 90, and 120 minutes, and the change of the concrete slump flow was repeatedly measured within the specified time. Before each concrete slump flow test, the concrete sample needs to be re-stirred and evenly mixed. Figure 4 The figure shows the initial slump expansion and slump expansion retention of concrete with modified natural chitosan biomass shrinkage reducer and concrete with commercial shrinkage reducer at different dosages. Figure 4 It can be seen that adding shrinkage reducers to concrete increases the initial collapse expansion of concrete. At the same shrinkage reducer dosage, the concrete added with modified natural chitosan biomass shrinkage reducer (197.5mm, 205.2mm, 211.7mm, 218.5mm) has a lower initial collapse expansion than the concrete added with commercial shrinkage reducer (200.9mm, 211.3mm, 220.5mm, 231.2mm). With the increase of placement time, the collapse expansion of concrete added with both shrinkage reducers gradually decreases, and the increase in shrinkage reducer dosage leads to a gradual decrease in the loss rate of concrete collapse expansion. At the same shrinkage reducer dosage, the fresh concrete added with modified natural chitosan biomass shrinkage reducer (27.04%, 20.86%, 19.04%, 17.57%) has a higher slump expansion loss rate than the fresh concrete added with commercial shrinkage reducer (25.19%, 18.84%, 16.04%, 14.84%).
[0073] 3.1.2 Setting time of fresh concrete
[0074] When testing the setting time of fresh concrete with M-Chitin-SRA shrinkage reducer and fresh concrete with commercial shrinkage reducer (SITREN-SRA), record the time of adding mixing water when mixing concrete. Use a 5mm sieve to screen out mortar from the fresh concrete sample, put the screened mortar into a 150mm×150mm×150mm test mold, use a vibrator to tamp the mortar in the test mold 35 times, and place the mortar sample on the penetration resistance test bench. Turn the hand wheel to make the end face of the probe on the penetration resistance tester contact the mortar surface. In 10±2s, insert the probe vertically to a depth of 25±2mm to record the maximum penetration resistance value. Measure the mortar penetration resistance value once every period of time until the penetration resistance value per unit area on the mortar is higher than 28MPa. Plot the penetration resistance-time curve with the penetration resistance value as the ordinate and the test time as the abscissa. When the penetration resistance value reaches 3.5MPa, the corresponding time is the initial setting time of concrete. When the penetration resistance value reaches 28MPa, the corresponding time is the final setting time of concrete. Figure 5 The figure shows the setting time of concrete with modified natural chitosan biomass shrinkage reducer and concrete with commercial shrinkage reducer at different dosages. Figure 5 It can be seen that with the increase of shrinkage reducer dosage, the initial setting time and final setting time of fresh concrete increase. At the same dosage, the concrete with modified natural chitosan biomass shrinkage reducer (295min, 376min, 513min, 576min and 465min, 587min, 655min, 714min) has shorter initial setting time and final setting time than the concrete with commercial shrinkage reducer (376min, 469min, 584min, 622min and 493min, 612min, 683min, 739min).
[0075] 3.2 Mechanical properties test of hardened concrete
[0076] 3.2.1. Compressive strength of hardened concrete
[0077] After curing for 3, 7, 28, and 90 days in a standard environment, 100 mm × 100 mm × 100 mm concrete specimens were placed on a YAW-3000 electro-hydraulic servo loading system at a loading rate of 1.3 MPa / s to measure the compressive strength of hardened concrete in accordance with the national standard “Standard for Test Methods of Mechanical Properties of Ordinary Concrete” (GB / T50081-2002). Figure 6 The figure shows the compressive strength of concrete mixed with modified natural chitosan biomass shrinkage reducer and concrete mixed with commercial shrinkage reducer at different dosages. Figure 6It can be seen that with the increase of curing time, the compressive strength of concrete with both shrinkage reducers increases. At the same curing age, as the amount of shrinkage reducer increases, the compressive strength of concrete with shrinkage reducer decreases. At the same dosage and curing age (1.5%, 2.0%-90 days), concrete with modified natural chitosan biomass shrinkage reducer (73.82MPa, 73.48MPa) has higher compressive strength than concrete with commercial shrinkage reducer (73.43MPa, 73.32MPa).
[0078] 3.2.2 Flexural strength of hardened concrete
[0079] The flexural strength of hardened concrete was tested by the three-point flexural method specified in the national standard "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2002). After 3, 7, 28, and 90 days of standard curing of 150mm×150mm×550mm prism concrete specimens, the specimens were placed with the molding surface facing upward on a DYE-300 fully automatic flexural testing machine, and the side of the prism concrete was loaded at a speed of 40N / s until the specimen broke, and the flexural strength of the hardened concrete was measured. Figure 7 The figure shows the flexural strength of concrete with modified natural chitosan biomass shrinkage reducer and concrete with commercial shrinkage reducer at different dosages. Figure 7 It can be seen that with the increase of curing time, the flexural strength of concrete with both shrinkage reducers increases. At the same curing age, with the increase of shrinkage reducer dosage, the flexural strength of concrete with shrinkage reducers decreases. At the same dosage and curing age (1.5%, 2.0%-90 days), concrete with modified natural chitosan biomass shrinkage reducer (9.59MPa, 9.55MPa) has higher flexural strength than concrete with commercial shrinkage reducer (9.45MPa, 9.42MPa).
[0080] 3.3 Concrete cracking
[0081] The crack resistance of concrete mixed with modified natural chitosan biomass shrinkage reducer was tested by the flat plate method according to the method specified in the national standard "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009). From the beginning of concrete pouring, the initial crack start time, total number of cracks, total length of cracks and total width of cracks of fresh concrete in the plastic stage for 24 hours, and the total crack area of concrete per unit area were recorded as indicators for evaluating the crack resistance of concrete. After the test started, it was observed every 5 minutes to determine the appearance time of the first crack of concrete. Within the first 4 hours of the appearance of the crack, it was measured every 30 minutes. When the crack penetrated the concrete surface, the appearance of the concrete surface crack was observed every 1 hour. The length of the crack on the concrete surface was measured using a soft wire, and the width of the crack on the specimen surface was measured using a 100x reading microscope. The width of the crack on the concrete surface was divided into three levels: 1.00mm, 0.75mm, and 0.50mm, and the length of the crack belonging to the corresponding width range was measured. The product of the crack width and length of the concrete specimen is the crack area. All crack areas are added together and the total crack area per unit area of concrete is calculated using formula (3).
[0082]
[0083] c=a×b(3)
[0084] Where: Wi is the maximum width of the ith crack (mm); L is the length of the ith crack (mm); N is the total number of cracks (roots); a is the average crack area (mm 2 / root); A-the area of thin plate (0.36m 2 ); b-Number of cracks per unit area (roots / m 2 ); c-total cracking area per unit area (mm 2 / m 2 ).
[0085] Figure 8 The figure shows the crack resistance of hardened concrete with modified natural chitosan biomass shrinkage reducer and hardened concrete with commercial shrinkage reducer at different dosages. It can be seen from the figure that with the increase of shrinkage reducer dosage, the initial crack start time of hardened concrete with two shrinkage reducers increases, and the total number of cracks, total crack length, total crack width, and total crack area per unit area are reduced. At the same shrinkage reducer dosage, concrete with modified natural chitosan biomass shrinkage reducer has a longer initial crack start time, less total number of cracks, total crack length, total crack width, and total crack area per unit area than concrete with commercial shrinkage reducer.
[0086] 3.4 Concrete shrinkage performance
[0087] 3.4.1. Concrete shrinkage
[0088] Concrete autogenous shrinkage test was carried out in accordance with the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T 50082-2009). After 24 hours of standard curing, the sealed concrete specimens were demolded. The surface of the demolded concrete specimens was sealed with a flexible polypropylene film in multiple layers, and then wrapped with a layer of aluminum foil to ensure that the copper heads on both sides of the concrete specimens were exposed. The rest of the parts were sealed to avoid moisture loss. After the sealing was completed, the concrete specimens were placed on a vertical micrometer stand, and the reference length of the specimens was measured with a comparator for 24 hours. The concrete test was placed in a constant temperature and humidity room with a temperature of 23±2℃ and a relative humidity of 50±5%, and aluminum foil was used to seal the top of the specimens to prevent the evaporation of concrete moisture. The length changes of the concrete specimens were measured at the corresponding ages (3, 7, 14, 21, and 28 days) to determine the autogenous shrinkage value of the concrete.
[0089] Fig. 9 The figure shows the autogenous shrinkage values of concrete mixed with modified natural chitosan biomass shrinkage reducer and concrete mixed with commercial shrinkage reducer at different dosages. Fig. 9 It can be seen that as the shrinkage time increases, the shrinkage of concrete with both shrinkage reducers increases. At the same shrinkage time, the increase in the amount of shrinkage reducer reduces the shrinkage of concrete. At the same shrinkage reducer dosage and the same shrinkage age (1.5%, 2.0%-28 days), concrete with modified natural chitosan biomass shrinkage reducer (0.08981%, 0.08527%) has a lower shrinkage value than concrete with commercial shrinkage reducer (0.09673%, 0.09235%).
[0090] 3.4.2 Concrete drying shrinkage
[0091] According to the method of "Testing Procedures for Hydraulic Concrete" (DL / T 5150-2001), the drying shrinkage value of the hardened concrete specimens added with modified natural chitosan biomass shrinkage reducer was tested. After the 75mm×75mm×285mm test mold was placed in a room with a temperature of 18-23℃ and a relative humidity of 60±5% for 24 hours, the concrete specimen was removed from the test mold and the reference length of the hardened concrete was measured. After the shrinkage head was buried in the corresponding hole of the test mold, the concrete specimen was placed in a shrinkage test box (temperature of 20-25℃, humidity of 50-55%), and the length change of the concrete specimen was measured for 1, 4, 7, 28, 56, 90, and 112 days. During the specified time of testing the length of the hardened concrete specimen, the concrete specimen was taken out of the shrinkage test box and placed in the air for 5-10 minutes. The drying shrinkage of hardened concrete is defined as the ratio of the length change of the concrete specimen added with modified natural chitosan biomass shrinkage reducer to the reference concrete length during the specified test age. Fig.10The figure shows the drying shrinkage of concrete with modified natural chitosan biomass shrinkage reducer and concrete with commercial shrinkage reducer at different dosages. Fig.10 It can be seen that as the drying time increases, the drying shrinkage of concrete with both shrinkage reducers increases. At the same drying time, the increase in the amount of shrinkage reducer leads to a decrease in the drying shrinkage of concrete. At the same shrinkage reducer dosage and the same drying age (1.5%, 2.0%-112 days), concrete with modified natural chitosan biomass shrinkage reducer (0.0465%, 0.0421%) has a lower drying shrinkage value than concrete with commercial shrinkage reducer (0.0552%, 0.0503%).
[0092] 3.5. Durability of concrete
[0093] 3.5.1. Water absorption of hardened concrete
[0094] The water absorption test of hardened concrete specimens was carried out in accordance with the ASTM C 642 standard developed by the American Society for Testing and Materials. The cylindrical concrete sample is placed in an oven at 100-110℃ and dried for 24 hours until constant weight is reached. After drying, the specimen is placed in an oven and cooled to room temperature before weighing. The cooled cylindrical concrete sample is placed in a constant temperature water tank (water temperature is 20±5℃) and soaked for 45 minutes. The cylindrical hardened concrete sample is taken out of the water, the surface adsorbed water of the cylindrical hardened concrete sample is wiped off and weighed. The water absorption rate of hardened concrete is the percentage of the total weight of water absorbed by the cylindrical sample in 45 minutes to the absolute dry weight of hardened concrete.
[0095] Fig.11 The figure shows the water absorption of hardened concrete mixed with modified natural chitosan biomass shrinkage reducer and hardened concrete mixed with commercial shrinkage reducer at different dosages at 28 and 90 days of curing age. Fig.11 It can be seen that with the increase of curing age, the water absorption of hardened concrete with two shrinkage reducers decreased. At the curing age of 28 and 90 days, with the increase of shrinkage reducer dosage, the water absorption of both hardened concrete decreased. At the same shrinkage reducer dosage and curing age (28 and 90 days), the hardened concrete with modified natural chitosan biomass shrinkage reducer (5.238%, 5.197%, 5.165%, 5.141% and 4.773%, 4.754%, 4.739%, 4.726%) has a lower water absorption than the hardened concrete with commercial shrinkage reducer (5.304%, 5.232%, 5.217%, 5.182% and 4.814%, 4.792%, 4.765%, 4.743%).
[0096] 3.5.2. Chloride ion penetration resistance of hardened concrete
[0097] The resistance of hardened concrete to chloride ion penetration is tested according to the electric flux method in the American Society for Testing and Materials ASTM C1202 standard. After standard curing for 28 and 90 days, the concrete samples were vacuum saturated with water for 24 hours in a concrete intelligent vacuum saturator. After vacuum saturation, the concrete samples were placed in a test tank. One side of the cylindrical concrete sample was in contact with a NaCl solution with a mass concentration of 3% (negative electrode), and the other side of the cylindrical concrete sample was immersed in a NaOH solution with a molar concentration of 0.3 mol / L (positive electrode). A 60V DC voltage was applied axially to the cylindrical specimen for 6 hours to force the chloride ions in the negative electrode to migrate to the positive electrode. The total charge passing through the concrete sample in 6 hours was recorded to evaluate the chloride ion penetration resistance of the hardened concrete sample. Fig.12 The figure shows the resistance of hardened concrete to chloride ion penetration at different dosages at 28 and 90 days of curing age, which is different from the hardened concrete with modified natural chitosan biomass shrinkage reducer and commercial shrinkage reducer. Fig.12 It can be seen that with the increase of curing age, the total charge of the hardened concrete samples with the addition of two shrinkage reducers in 6 hours decreases. At the curing age of 28 and 90 days, with the increase of the amount of shrinkage reducer, the total charge of the two concrete samples in 6 hours decreases. At the same shrinkage reducer dosage and the same curing age (28, 90 days), the concrete added with modified natural chitosan biomass shrinkage reducer (2047.3C, 1913.5C, 1809.7C, 1695.2C and 1249.7C, 1156.1C, 1116.9C, 1473.3C) has a lower total charge (6 hours) than the hardened concrete added with commercial shrinkage reducer (2099.4C, 1987.3C, 1905.1C, 1807.2C and 1378.9C, 1243.1C, 1177.3C, 1103.9C). The hardened concrete added with modified natural chitosan biomass shrinkage reducer has lower chloride ion permeability than the hardened concrete added with commercial shrinkage reducer.
Claims
1. A method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent by modifying natural biomass chitin, characterized in that: The following steps are involved: (1) heating and stirring a chitosan polymer and water to obtain a suspension, acidifying the suspension and then treating it with chitinase to obtain a chitosan oligomer solution, wherein the weight average molecular weight of the chitosan oligomer is controlled to be between 8435 and 8678; (2) Sodium dihydrogen phosphate is added to the chitosan oligomer solution and the pH value is adjusted to 2-3, and a phosphating reaction is carried out in a microwave reactor to obtain chitosan phosphate derivative oligomers. After the reaction is completed, the chitosan phosphate oligomer solution is taken out from the microwave reactor, the temperature is raised to 65-70°C, and a sodium hydroxide solution is added to adjust the pH value of the system to 12-13. The solution is rapidly stirred at 65-70°C for 8-10 hours to remove the acetyl group in the chitosan phosphate oligomer to obtain a chitosan oligomer solution containing amino and phosphate groups, and the deacylation degree of the chitosan phosphate oligomer molecules is controlled at 88-92%; (3) slowly adding the chitosan oligomer solution containing amino groups and phosphate groups prepared in step (2) to the methyl allyl alcohol polyoxyethylene ether solution, and completing the addition over 30-40 minutes, slowly adding the catalyst p-toluenesulfonic acid, and raising the temperature to 120-130° C. At this temperature, the hydroxyl groups on the methyl allyl alcohol polyoxyethylene ether and the amino groups on the phosphate chitosan oligomer undergo hydroxylation reaction for 6-8 hours to obtain a light yellow oily chitosan oligomer solution containing double bonds, phosphate groups, and ether groups; (4) adding the chitosan oligomer solution containing double bonds, phosphate groups and ether groups prepared in step (3) to the 1,2-epoxy-4-vinylcyclohexane aqueous solution at a temperature of 40-45°C, continuously stirring, adjusting the pH value of the system to 10-11, maintaining the solution temperature at 65-70°C, slowly dropping ammonium persulfate and manganese pyrophosphate composite initiator over 20-30 minutes, raising the system temperature to 90-95°C, and graft copolymerizing at 90-95°C for 3-4 hours; (5) After the reaction is completed, the reactant solution is naturally cooled to ambient temperature, and then aged in a reaction vessel for 2-3 hours, and the pH value is adjusted to 10-11 to prepare a light yellow hyperbranched, non-ionic modified natural biomass chitosan shrinkage reducer with a solid content of 15-18% and containing -OH, -NH2, -OPO3Na, -R1OR2, and -CH2(O)CH2 groups.
2. The method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent using modified natural biomass chitosan according to claim 1, characterized in that: The weight ratio of chitosan polymer to water in step (1) is 1:1.6; the acidification temperature is 25-30°C, the pH is 4-5, and the acidification treatment takes 20-30 minutes.
3. The method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent using modified natural biomass chitosan according to claim 1, characterized in that: In step (1), the amount of chitinase used is 2.45-2.50 wt% of the amount of chitin polymer used, the chitinase treatment temperature is -5-0°C, and stirring is continued for 8-10 hours.
4. The method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent using modified natural biomass chitosan according to claim 1, characterized in that: In step (2), the weight ratio of the chitosan oligomer solution to sodium dihydrogen phosphate is 39.5:1-40.0:1, the radiation reaction power of the microwave reactor is 150W, the maximum radiation reaction temperature is 95°C, The radiation reaction time is 20 minutes.
5. The method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent using modified natural biomass chitosan according to claim 1, characterized in that: In step (3), the weight ratio of methyl allyl alcohol polyoxyethylene ether to the chitosan oligomer solution containing amino and phosphate groups is 1: 2.75-2.80, and the amount of p-toluenesulfonic acid used is 2.23-2.24 wt % of the amount of methyl allyl alcohol polyoxyethylene ether used.
6. The method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent using modified natural biomass chitosan according to claim 1, characterized in that: In step (4), the weight ratio of 1,2-epoxy-4-vinylcyclohexane to the chitosan oligomer solution containing double bonds, phosphate groups, and ether groups is 1:60.1-60.2, and the amount of ammonium persulfate and manganese pyrophosphate composite initiator is 1.50-1.51 wt % of the amount of the chitosan oligomer solution containing double bonds, phosphate groups, and ether groups, wherein the weight ratio of ammonium persulfate to manganese pyrophosphate is 1:
1.
7. The method for preparing a hyperbranched, nonionic concrete shrinkage reducing agent by using modified natural biomass chitosan according to claim 1, characterized in that: Step (5) further comprises placing the modified natural biomass chitosan shrinkage reducing agent solution in an oven, drying it at a temperature of 90-95° C. for 16-24 hours to obtain a solid shrinkage reducing agent, crushing and ball-milling the solid shrinkage reducing agent, and passing it through a 0.40 mm round hole sieve to obtain a modified natural biomass chitosan shrinkage reducing agent powder having a particle size of less than 0.40 mm.
8. The modified natural biomass chitosan shrinkage reducing agent prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the modified natural biomass chitosan shrinkage reducing agent according to claim 8 in preparing concrete.
10. The use according to claim 9, characterized in that: The modified natural biomass chitosan shrinkage reducing agent is added in an amount of 0.5-2.0 wt %.
Citation Information
Cited By
Microwave-assisted deep-eutectic solvent extraction-cation modified chitin integrated preparation method, modified chitin and application
CN121736138A